Distortion-product otoacoustic emissions measured using synchronized swept-sines - Vencovský, Václav; Novak, Antonin; Klimeš, Ondřej; Honzík, Petr; Vetešník, Aleš (The Journal of the Acoustical Society of America, 2023)
Swept-sines provide a tool for fast and high-resolution measurement of evoked otoacoustic emissions. During the measurement, a response to swept-sine(s) is recorded by a probe placed in the ear canal. Otoacoustic emissions can then be extracted by various techniques, e.g., Fourier analysis, the heterodyne method, and the least-square-fitting (LSF) technique. This paper employs a technique originally proposed with exponential swept-sines, which allows for direct emission extraction from the measured intermodulation impulse response. It is shown here that the technique can be used to extract distortion-product otoacoustic emissions (DPOAEs) evoked with two simultaneous swept-sines. For proper extraction of the DPOAE phase, the technique employs previously proposed adjusted formulas for exponential swept-sines generating so-called synchronized swept-sines (SSSs). Here, the SSS technique is verified using responses derived from a numerical solution of a cochlear model and responses measured in human subjects. Although computationally much less demanding, the technique yields comparable results to those obtained by the LSF technique, which has been shown in the literature to be the most noise-robust among the emission extraction methods.
Keywords: Otoacoustic Emissions, Spontaneous; Cochlea; Humans; zvukovod; Ear Canal; lidé; Fourier Analysis; Fourierova analýza; kochlea; otoakustické emise spontánní